2021
DOI: 10.1063/5.0037411
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of GTR (generation–transport–recombination) in semiconductor simulations

Abstract: With the emergence of phase change memory, where the devices experience extreme thermal gradients (∼100 K/nm) during transitions between low and high resistive states, the study of thermoelectric effects at small scales becomes particularly relevant. We had earlier observed asymmetric melting of self-heated nano-crystalline silicon micro-wires, where current densities of ∼107 A/cm2 were forced through the wires by 1 μs, ∼30 V pulses. The extreme asymmetry can be explained by the generation of considerable amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…An analysis of bipolar effects can be found in ref. [75], where a semiconductor approach is used to simulate carrier dynamics and energy exchanges.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of bipolar effects can be found in ref. [75], where a semiconductor approach is used to simulate carrier dynamics and energy exchanges.…”
Section: Discussionmentioning
confidence: 99%
“…Qian et al demonstrated that in high current and thermal breakdown stages, the effects of recombination and Thomson heat become more pronounced [16]. Muneer et al presented the thermal behaviors of different types heat in the self-heated nano-crystalline silicon micro-wires under asymmetric melting, revealing that the maximum electronic-convective heat power increases to five times the Joule heat after melting [17]. Shang et al stated that under optimal voltage in photovoltaic devices, the combined power consumption from Peltier heat and surface recombination heat equaled half of Joule heat [18].…”
Section: Introductionmentioning
confidence: 99%